Konsumsi Inhibitor dan Enhencer Zat Besi Sebagai Faktor Risiko Terjadinya Anemia Pada Remaja Putri Di Kota Semarang - Susantini, Purwanti; Bening, Salsa (Universitas Muhammadiyah Semarang, 2023)
The prevalence of anemia in adolescent girls aged 15-24 years is 32%, the impact is lack of concentration in receiving lessons at school, often not attending school, stunted physical growth, decreased immunity, susceptible to infection, and reduced productivity. The purpose of this study was to analyze the consumption of iron inhibitors and diluents as a risk factor for the incidence of anemia in adolescent girls in the city of Semarang. The type of research is observation with case control design, hemoglobin level examination using cyanmethemoglobin method, consumption of enhancers and enhancers using Semi Quantitative Food Frequency Questinore. Analysis using Chi Square. The prevalence of anemia in Semarang City is 29.59%. There is relathionship inhibitor consumption with the incident of anemia in adolescent girls (p= 0.004 ), and inhobitors as a risk factor for anemia in adolescent girls (OR = 4.94). Enhancers were not retathionship with the incident of anemia in adolescent and not a risk ( p = 0,18, OR= 0,49). Relathionship inhibitor with anemia and .Enhancers were not a risk factor for anemia in adolescent girls. Improvement of food consumption for adolescent girls by reducing consumption of inhibitors. Keywords: Inhibitors, enhancers, young women